Council-manager plan the experience of Western Nigeria - Oyediran, Oyeleye (Philippine Journal of Public Administration, 1977)
In the 60's, the Western Nigerian government tended to emphasize efficiency and viability in government rather than responsiveness to people's demands in the face of revolutionary changes and discontent over the system of local administration Thus, the council-manager model of local government, an American political creation, was adopted in 1973 not only to cope with the problems of the old system but also to establish something close to the ideal of "good government." This article examines the background to the adoption of this system, the structural design, how it worked, and why it failed; problems of institutional transfer and the willingness to break away from traditional experiences, structures and attitudes are traced as causes or reasons for failure.